A method of designing swinging-leg walking trajectory for biped robot on plat ground. (17th April 2023) - Shu, Yingli; Yuan, Quande; Zhang, Jian; Li, Huazhong; Pi, Yuzhen; Ke, Wen-de
The periodic walking of biped robot involves the alternate movement of supporting leg and swinging leg. In order to quickly plan the gait, it is necessary to select the key posture of biped walking on the premise of maintaining the stability of the robot. Based on the known information, the spline curve is designed and solved to construct the ankle trajectory of the swinging leg of the robot. Simulation results showed the feasibility of the method.